Climate change and water resources - Grady, Caitlin A.; Younos, Tamim (The Handbook of Environmental Chemistry, 2013)
This volume presents nine chapters prepared by international authors and highlighting various aspects of climate change and water resources. Climate change models and scenarios, particularly those related to precipitation projection, are discussed and uncertainties and data deficiencies that affect the reliability of predictions are identified. The potential impacts of climate change on water resources (including quality) and on crop production are analyzed and adaptation strategies for crop production are offered. Furthermore, case studies of climate change mitigation strategies, such as the reduction of water use and conservation measures in urban environments, are included. This book will serve as a valuable reference work for researchers and students in water and environmental sciences, as well as for governmental agencies and policy makers.